2017
DOI: 10.1111/ane.12736
|View full text |Cite
|
Sign up to set email alerts
|

Risk of stroke after bereavement-a systematic literature review

Abstract: Several studies have suggested that psychological stress may increase the risk of stroke. However, this link remains a controversial issue because of conflicting findings. Bereavement, the loss of a close relative, is considered a severely stressful life event. Increased risk of stroke could thus be expected after bereavement if stress plays a causal role. We aimed to evaluate the association between bereavement and stroke by performing a systematic review of the existing literature. The literature search was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Our findings are in line with several earlier studies showing a 9%-140% increased risk of stroke in persons exposed to the death of a spouse, sibling, or an unspecified relative. 6 Similarly, our results are also comparable to associations reported between other psychosocial factors such as work stress, anxiety, and depression and the risk of stroke. [10][11][12][13][14][15] Our findings corroborate studies 1-5 that showed increased risks of acute myocardial infarction, atrial fibrillation, heart failure, and death due to CVD among bereaved parents.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings are in line with several earlier studies showing a 9%-140% increased risk of stroke in persons exposed to the death of a spouse, sibling, or an unspecified relative. 6 Similarly, our results are also comparable to associations reported between other psychosocial factors such as work stress, anxiety, and depression and the risk of stroke. [10][11][12][13][14][15] Our findings corroborate studies 1-5 that showed increased risks of acute myocardial infarction, atrial fibrillation, heart failure, and death due to CVD among bereaved parents.…”
Section: Discussionsupporting
confidence: 89%
“…A recent systematic review suggests that the death of a close family member is associated with an increased risk of stroke; however, the majority of the 6 studies included in the review focused on spousal bereavement. 6 To our knowledge, only one study has so far investigated the link between the death of a child aged <18 years and stroke; its finding of no association might be due to the fact that parents were too young to experience stroke at the end of the follow-up. 7 In this population-based cohort study with a long follow-up period (up to 39 years), we investigated whether parents who lost an offspring had an increased risk of stroke, and if so, whether the risk differed by characteristics of the child's death, time since death, and sociodemographic factors of the family or according to subtypes of stroke.…”
mentioning
confidence: 98%
“…Losing a spouse can be a very stressful life event that places individuals at risk for mental and physical health problems (1,2). Particularly in the immediate weeks and months following spousal loss, bereavement is associated with increased risk of multimorbidity and mortality (2-5), including an elevation in inflammation-related health problems (6-10), cardiovascular disease (CVD) (8, [11][12][13][14], and some types of cancer (12). Despite a large body of research in the trauma literature attempting to identify risk factors for adverse health outcomes following spousal bereavement, however, the mechanisms through which mental and physical health problems emerge following interpersonal loss remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Such an attachment loss typically leads to acute grief symptoms that include yearning and longing for the loved one; intrusive thoughts and avoidance of reminders of the deceased; sadness and other painful emotions; loneliness, shock and disbelief; and emotional numbness (Shear, 2012;Shear et al, 2013;Simon, 2013). Bereavement among the elderly is associated with precipitating or worsening of mental disorders; decrements in physical health; and increased risk of hospitalization; cardiovascular risk; and premature mortality (Aalbaek et al, 2017;Ennis and Majid, 2019;Stroebe et al, 2007). Most individuals successfully adapt to the emotional consequences of bereavement without seeking mental health care.…”
Section: Introductionmentioning
confidence: 99%